The SNAP-tag technology revised: an effective chemo-enzymatic approach by using a universal azide-based substrate. (1st January 2021) - Merlo, Rosa; Caprioglio, Diego; Cillo, Michele; Valenti, Anna; Mattossovich, Rosanna; Morrone, Castrese; Massarotti, Alberto; Rossi, Franca; Miggiano, Riccardo; Leonardi, Antonio; Minassi, Alberto; Perugino, Giuseppe
Abstract: SNAP- tag ® is a powerful technology for the labelling of protein/enzymes by using benzyl-guanine (BG) derivatives as substrates. Although commercially available or ad hoc produced, their synthesis and purification are necessary, increasing time and costs. To address this limitation, here we suggest a revision of this methodology, by performing a chemo-enzymatic approach, by using a BG-substrate containing an azide group appropriately distanced by a spacer from the benzyl ring. The SNAP- tag ® and its relative thermostable version ( Ss OGT- H 5 ) proved to be very active on this substrate. The stability of these tags upon enzymatic reaction makes possible the exposition to the solvent of the azide-moiety linked to the catalytic cysteine, compatible for the subsequent conjugation with DBCO-derivatives by azide-alkyne Huisgen cycloaddition. Our studies propose a strengthening and an improvement in terms of biotechnological applications for this self-labelling protein-tag .